How to be a decisive leader : improve your decision-making and problem-solving skills - Hall, Richard, 1964- (Business express series., 2015)
If you need to be in the know in no time at all, Business Express will get you from beginner to brilliant in the blink of an eye. This fast, focused and carefully crafted eBook will help you pick up all the essential knowledge you need about the skills that matter most at work, all in the shortest possible time. Learn just when you need to or well in advance; read it at your desk or on the move; dip in and out or start from scratch - it's all up to you. But however you use it, you'll quickly feel more confident, competent and better equipped to make things happen and keep moving ahead. Save time - it's quick and easy to read Get smart - just the essential knowledge you need Feel good - watch your confidence grow Business Express - know how in no time! It'll only take about 30 minutes for you to get up to speed on one of these other great Business Express subjects too. Seach by title, download your copies and start knowing more in no time: Managing Your Time Productively Developing Your Influencing Skills Delegating Effectively Managing Upwards Successfully Persuasive Communication Leading Your Team Through Change Making Effective Decisions Managing Performance and Appraisals Managing Difficult Situations and Discussions Negotiating With Confidence Writing Compelling Reports and Proposals Presenting With Confidence How to be Assertive Effective Mentoring Coaching Effectively Managing Productive Meetings Motivating Your Team Embracing Diversity Within Your Team Effective Problem Solving Interviewing With Confidence How to be a Great Leader Your first 60 days as a Leader Establish Yourself as a Leader Communicate Like a Leader Set Your Leadership priorities Lead Your Team Nurturing Business Innovation Sharpen Your Influencing Strategies How to be a Decisive Leader: Inspire Your Team to Change How to be a Successful Change Leader Making Strategic Business Change decisions Create a Successful Change Strategy How to Build Your Vision for Change Promote a Positive Change Culture How to Create an Action Plan for Change How to Communicate Change to Your Team Managing Resistance to Change Support Your Team through Change Sustaining Business Change.